1979
DOI: 10.1017/s0021859600053855
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative digestion of fresh herbage by sheep:V. The digestion of four herbages and prediction of sites of digestion

Abstract: The extents and sites of digestion of organic matter (OM), and its constituent watersoluble carbohydrates, organic acids, pectin, cellulose, hemicellulose and crude protein have been studied in sheep prepared with re-entrant duodenal cannulas and fed four fresh herbage diets, Ruanui perennial ryegrass, Tama Westerwolds ryegrass, Pitau white clover and Fakir sainfoin, at each of two levels of intake.The water-soluble carbohydrate, organic acids and pectin of all diets were almost completely digested within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 37 publications
5
40
1
2
Order By: Relevance
“…As stated previously, diets R1, W1 and W2 were all characterized by high contents of N, and on the basis of studies by Mangan (1982) and Ulyatt et al (1985) it appears reasonable to conclude that much of this N would be rapidly released during mastication and thus readily degraded in the rumen. From the present results it may be estimated that degraded N: degraded OM values varied between 45 g/kg (Rl) and 62 g/kg (white-clover diets), all of which would on the basis of current knowledge supply adequate degraded N to support active and efficient microbial growth.…”
Section: Discussionsupporting
confidence: 52%
“…As stated previously, diets R1, W1 and W2 were all characterized by high contents of N, and on the basis of studies by Mangan (1982) and Ulyatt et al (1985) it appears reasonable to conclude that much of this N would be rapidly released during mastication and thus readily degraded in the rumen. From the present results it may be estimated that degraded N: degraded OM values varied between 45 g/kg (Rl) and 62 g/kg (white-clover diets), all of which would on the basis of current knowledge supply adequate degraded N to support active and efficient microbial growth.…”
Section: Discussionsupporting
confidence: 52%
“…Third the incidence of bloat, as seen with legume diets, may in part be related to the rapid rates of digestion and protein solubilization of fresh forage which occur in the rumen following ingestion (Beever et al 19866). In these regards the results of the present experiment with respect to the untreated forages confirm previous experimental findings (Beever et al 1985(Beever et al , 1986aUlyatt et al 1981).…”
Section: Discussionsupporting
confidence: 86%
“…Recent experiments with growing cattle (Ulyatt et al 1981;Beever et al 1985Beever et al , 1986a have demonstrated that as the amount of nitrogen in the crop increases, considerable losses of N between mouth and duodenum (up to 0.40 of N intake) can occur. Such losses have been associated with high rumen ammonia concentrations and it has been concluded that both are associated with the relatively large amounts of soluble N in fresh forages and the consequent imbalance between degraded N and degraded organic matter (OM) supply in the rumen.…”
mentioning
confidence: 99%
“…Kraiem et al (1990) observed no differences between lucerne, birdsfoot trefoil and sainfoin when compared as hays or silage harvested at the early flowering stage. Comparing fresh sainfoin and white clover at the vegetative stage, Ulyatt and Egan (1979) found a lower OMD for sainfoin (76% v. 84%), but white clover is known to be more digestible than lucerne.…”
Section: Energy Value and Ingestibilitymentioning
confidence: 94%